Genetics of yield and yield components in pumpkin (Cucurbita moschata) - MOHANTY, B K; MOHANTY, S K; MISHRA, R S (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during 1994-95 to study an 8 Ã— 8 half diallel cross of pumpkin (Cucurbita moschata Duch.ex.Poir.)for yield and its attributing traits at 2 locations. The pooled analysis revealed pre-ponderance of dominance and non-additive gene action for all the characters supported by low heritability in narrow sense. Pronounced epistasis was observed for number of female flowers and fruits, average fruit weight and yield/plant. Over dominancewas prevalent for all the traits. Frequent occurrence of dominant genes among parents for vine length and flesh thickness and recessive genes for the remaining characters were indicated. Most dominant genes exerted positive effect. However, unequal distribution of positive and negative alleles showing dominancein parents was recorded for all the characters except number of primary branches/plant. Polygenic inheritance of yield and yield contributing characters were detected. Heterosis breeding was suggested for improvement of yield and yield components in pumpkin.